Analisis Persepsi Mahasiswa Universitas HKBP Nommensen Medan terhadap Pelayanan Transportasi Grab di Kota Medan - Efarnia Zai, Lema; Pasaribu, Jhonson; Panjaitan, Maringan (Journal of Comprehensive Science, 2025)
The advancement of digital technology has significantly transformed the transportation sector, including the emergence of app-based transportation services such as Grab. As one of the leading online transportation providers, Grab offers easy access, flexibility, and features designed to enhance user convenience. In Medan, this service is widely used by university students as a daily transportation alternative. However, students' perceptions of Grab's service quality vary, particularly regarding safety, comfort, punctuality, and ease of application use. This study aims to analyze the perceptions of Universitas HKBP Nommensen Medan students regarding Grab's transportation services based on these three main aspects. Using a qualitative research method with a descriptive approach, data were collected through in-depth interviews with student users. The findings indicate that students generally perceive Grab as a relatively safe and comfortable transportation service, supported by GPS features and driver identification systems that enhance user trust. However, challenges remain in the accuracy of estimated arrival times due to traffic conditions. Additionally, while the Grab app is considered user-friendly, technical issues such as network disruptions and fare surges during peak hours persist. Therefore, periodic service evaluations, improved accuracy in time estimation, and application network optimization are necessary to enhance the user experience.